Bias in dissemination of clinical research findings: structured OPEN framework of what, who and why, based on literature review and expert consensus. Issue 1 (21st January 2016) - Bassler, Dirk; Mueller, Katharina F; Briel, Matthias; Kleijnen, Jos; Marusic, Ana; Wager, Elizabeth; Antes, Gerd; von Elm, Erik; Altman, Douglas G; Meerpohl, Joerg J
Abstract : Objective: The aim of this study is to review highly cited articles that focus on non-publication of studies, and to develop a consistent and comprehensive approach to defining (non-) dissemination of research findings. Setting: We performed a scoping review of definitions of the term 'publication bias' in highly cited publications. Participants: Ideas and experiences of a core group of authors were collected in a draft document, which was complemented by the findings from our literature search. Interventions: The draft document including findings from the literature search was circulated to an international group of experts and revised until no additional ideas emerged and consensus was reached. Primary outcomes: We propose a new approach to the comprehensive conceptualisation of (non-) dissemination of research. Secondary outcomes: Our 'What, Who and Why?' approach includes issues that need to be considered when disseminating research findings (What?), the different players who should assume responsibility during the various stages of conducting a clinical trial and disseminating clinical trial documents (Who?), and motivations that might lead the various players to disseminate findings selectively, thereby introducing bias in the dissemination process (Why?). Conclusions: Our comprehensive framework of (non-) dissemination of research findings, based on the results of a scoping literature search and expert consensus will facilitate the development of future policies and guidelines regarding the multifaceted issue of selective publication, historically referred to as 'publication bias'.